Desain Reaktor Dehidrogenasi Pada Praprancangan Pabrik Linier Alkil Benzen (LAB) Dari Benzen Dengan Proses Uop/Cepsa (Detal Process) - Khalya Fathonah (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Linear Alkyl Benzene (LAB) is one of the organic chemicals in the form of clear liquids with the formula of mokelul C6H5CnH2n+1. LAB is used as raw material in detergent industry. LAB is chosen because it has a high rate of degradation so it is environmentally friendly (biodegradable). In 1995, UOP/CEPSA introduced a method of creating LAB using solid catalysts, called Detal Process. Due to higher yields, product quality and lower production costs, this process is considered better. Lab factory design capacity is 80,000 tons/year with the flow rate of incoming feeds and products of 4,5243.298 kg/h, in order to meet the needs of LAB in Indonesia which is 20% still exporting from abroad. One of the main tools used to produce LAB is a dehydrogenation reactor with a type of fixed bed multi-tube that serves to convert di-olefin into mono-olefin. The process is carried out at a temperature of 450oC and a pressure of 300 kPa (abs) with the help of platinum catalysts (Pt) in the liquid phase. The conversion rate of the reaction is 18% and the product is a mixture of mono-olefin, di-olefin, aromatic, hydrogen and paraffin. The type of reactor used is fixed bed multi-tube with lid and base elliptical head, and the buffer in the form of skirt support. The reactor is designed with a height of 9.76 m and a diameter of 6.08 m. In addition, the dehydrogenation reactor is equipped with steam as its internal heater.Keywords : Dehydrogenation, Elliptical Head, Fixed Bed Multitube, Linear Alkyl Benzene, Platina Catalyst